2014
DOI: 10.1186/s13054-014-0719-2
|View full text |Cite
|
Sign up to set email alerts
|

The arterial blood pressure associated with terminal cardiovascular collapse in critically ill patients: a retrospective cohort study

Abstract: IntroductionLiberal and overaggressive use of vasopressors during the initial period of shock resuscitation may compromise organ perfusion and worsen outcome. When transiently applying the concept of permissive hypotension, it would be helpful to know at which arterial blood pressure terminal cardiovascular collapse occurs.MethodsIn this retrospective cohort study, we aimed to identify the arterial blood pressure associated with terminal cardiovascular collapse in 140 patients who died in the intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The continuous LBNP profile allows us to take each subject to a state of intolerance to central blood loss (Fig. 4C) and subsequently the point of decompensation (i.e., depletion of the compensatory reserve) that replicates the terminal cardiovascular collapse observed in critically ill patients (52). This tolerance point is extremely reproducible in experiments repeated in the same individuals over both acute (< 1 h) and chronic (> 1 year) time periods (53,54).…”
Section: A Model With a Reproducible Clinical Outcomementioning
confidence: 97%
“…The continuous LBNP profile allows us to take each subject to a state of intolerance to central blood loss (Fig. 4C) and subsequently the point of decompensation (i.e., depletion of the compensatory reserve) that replicates the terminal cardiovascular collapse observed in critically ill patients (52). This tolerance point is extremely reproducible in experiments repeated in the same individuals over both acute (< 1 h) and chronic (> 1 year) time periods (53,54).…”
Section: A Model With a Reproducible Clinical Outcomementioning
confidence: 97%
“…Maintaining sufficient cardiac perfusion is of major importance during and immediately after cardiac arrest. 7 Data have suggested that a mean arterial pressure less than 45 mm Hg is associated with a significantly increased likelihood of hemodynamic collapse among ill patients 8 and is associated with increased mortality and decreased functional recovery in patients after cardiac arrest. [1][2][3] During the post-arrest period, patients are at high risk of re-arrest, and it is important to ensure sufficient coronary perfusion to reduce this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Both epinephrine and phenylephrine can be considered in the management of significant transient or sustained hypoperfusion. Although the definition of significant hypotension is complex, Brunauer et al 6 have suggested that a mean arterial pressure (MAP) of approximately 35 mm Hg is associated with a significant risk of CV collapse. Of course, a MAP of 40 to 50 mm Hg is also very concerning clinically, with significant risk of deterioration and CV collapse.…”
Section: Indicationsmentioning
confidence: 99%